MENGATASI MASALAH KECANDUAN GAME ONLINE DENGAN KONSELING BEHAVIORISTIK TEKNIK SELF MANAGEMENT PADA SISWA KELAS X SMA 1 MEJOBO - Alyana, Adinda Ayu; Santoso, Santoso; Hidayati, Richma (Jurnal Muria Research Guidance and Counseling (MRGC), 2024)
This research was carried out at SMA 1 Mejobo, using descriptive qualitative research using a case study type of research which requires data from research objects and subjects. clearly and realistically. The data collection techniques used in this research were observation, interviews and documentation which were explored in depth in order to obtain accurate data on the causes of online game addiction experienced by Mejobo 1 High School students. The research subjects taken were two students of class X and other supporting sources such as the counseling teacher, homeroom teacher, and the client's classmates. From the discussion above, it can be concluded that the counselor chooses to use behavioristic counseling, this self-management technique can solve the online game addiction problem that is being experienced by the client. counseling that is carried out between counselor and client cannot be resolved directly with one meeting, but with several counseling processes. Based on the results of the research that the researchers had done at SMA 1 Mejobo, the researchers provided advice to several parties, namely the Principal, Counseling Teachers, Students, and suggestions for the researchers themselves.